The Building a Religious Work Culture in Improving Employee Performance Quality - Herman; Rena Juliana; Khairuddin Hasan; Adi Kasman; Maya Agustina (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
This article is aimed to analyze the building a religious work culture in improving the quality of employee performance. Building a religious work culture based on the values ​​of Islamic teachings in managing educational resources. This study used a qualitative approach with a phenomenological type in understanding the meaning behind the phenomena that occur when building a religious culture in improving the quality of employee performance. The collecting data through observation, interviews, and study of the report documents of madrasa administration activities. Meanwhile, data processing techniques were carried out in stages starting from the data collection stage, data reduction, data presentation and up to the stage of drawing conclusions from the results of the study. The results showed that the leadership of the education unit has guided and nurtured employees with full sincerity in improving their performance. The duties and responsibilities entrusted to him have been carried out in accordance with his mandate, except in terms of the courage to work and innovate which still needs to be improved. Then the attitude of istiqamah to uphold religious law and government regulations has been consistent in improving the quality of its performance. This study implies that building a religious work culture can guarantee the quality of employee performance in providing academic administrative services to students as customers (consumers) of education. Keywords: Religious Work Culture, Employee Performance Quality, Education Personnel